Study of incidence of peptic ulcer perforation in young adults - Bansod, Atish; Bansod, Shubhangi A.; Galande, Ashok B.; Shamkuwar, Ambrish T.; Singh, Kamalkant H. (International Surgery Journal, 2016)
Background: Peptic ulcer perforation is the commonest perforation of the gastrointestinal tract affecting 2-10% population showing a shift from older to the younger population. With this statistics a study for incidence of peptic ulcer perforation in young adults 18-30 years was carried out. Methods: Prospective study of patients admitted on emergency basis and diagnosed as peptic ulcer perforation either gastric or duodenal perforation intraoperatively in patients 18-30 years were studied from June 2009 to October 2011. Results: Of 175 patients, 70 (40%) patients were between 18 and 30 years age. 58 (82.85%) were males and 12 (17.14%) were females. Twenty-three (32.85%) patients had history suggestive of acute peptic disease/ulcer and had taken some treatment in the form of antacid H-2 blocker or proton pump inhibitor while 47 (67.14%) patients had no history. Pain was the consistent symptom while tachycardia, tenderness, and guarding were the signs present in all 70 (40%) patients. Gas under diaphragm (pneumoperitoneum) was found in 67 (95.71%). Ultrasonography abdomen S/O pyoperitoneum was found that all 70 (100%). 57 (81.42%) patients had an anterior duodenal perforation, 12 (17.14%) patients had a gastric perforation with a ratio of 4.7:1, and 1 patient had a combined gastric and duodenal perforation. 1 (2.43%) patient expired in the post-operative period, 55 (78.57%) patients come for regular follow and 14 (20%) patients were lost to follow-up. Only 4 (7.2%) patients had mild to moderate symptoms of peptic ulcer disease which were controlled by anti-ulcer drugs. Conclusion: Peptic ulcer perforation is a disease more common in the young population with a male preponderance.